An Analysis of Land Use Pattern and Cropping intensity of District Maharajganj, Uttar Pradesh - Chaurasia, Ashutosh Kumar; Rai, Gayatri (National Geographical Journal of India, 2022)
Land as a factor of production has immense importance. Land may be rightly called the original source of all material wealth. Land is used for agricultural,industrial, recreational purpose. So land is most important natural resource. Therefore the study of land use / land cover pattern of a region is an outcome of the natural and socio-economic factor and their utilization by man in time and space. Land is becoming scarce due to immense agricultural activities and demographic pressure. Being a scarce resource it is necessity to use the land in a sustainable way. The study of land use is the integral part of geographical study. Land use is the actual and specific use to which the land surface is put in terms of inherent land use characteristics. Land use and land cover (LU/LC) in Maharajganj district has undergone constant change over the past two decades. Major changes caused by anthropogenic and natural factors have impacted regional environment and climate of the study area. Keeping this fact in view, an attempt has been made here to study the distribution and change in utilization of land under various categories in Maharajganj district lying in Tarai tract. This study is mainly based on secondary source of data collected from various government publications. Appropriate methodology is used for tabulation of data, mapping and graphical representation. Land use data has been analysed at block level using statistical tools and techniques. The result show that general land use is dominated by cultivated land (68.54%). Findings of the study may be helpful for sustainable utilization of land resource